Pest categorisation of Lepidosaphes pistaciae - EFSA Panel on Plant Health (PLH); Antonio Vicent Civera; Paula Baptista; Anna Berlin; Elisavet Chatzivassiliou; Jaime Cubero; Nik Cunniffe; Eduardo de la Peña; Nicolas Desneux; Francesco Di Serio; Anna Filipiak; Paolo Gonthier; et al. (EFSA Journal)
Abstract Following the commodity risk assessment of Prunus persica and P. dulcis plants for planting from Türkiye, in which Lepidosaphes pistaciae (Hemiptera: Diaspididae), the pistachio oyster scale or yellow pistachio scale, was identified as a pest of possible concern, the EFSA Panel on Plant Health performed a pest categorisation for the territory of the European Union (EU). L. pistaciae is reported as a polyphagous pest which, however, mainly affects plants of the genus Pistacia. Originating from Asia, it is widely distributed in pistachio producing countries of Central, South and West Asia. Within the EU, the pest has been reported from Cyprus and Greece. However, its precise distribution within Cyprus and Greece is unknown. It completes two generations per year and overwinters as a fully developed adult female. The eggs are hidden under the female's body and hatch around April. First‐instar nymphs, crawlers, move on host plants for a short period of time before becoming permanently settled and initiating feeding, mainly on leaves but also on branches and fruits. Young females appear in early June and mature ones in late June. Plants for planting and fruits provide potential pathways for entry into the EU. Climate suitability suggests that it could further establish in large parts of the EU. In Iran, L. pistaciae is considered a devastating pest for cultivated pistachio. L. pistaciae was detected in Greece over 30 years ago with small population densities and without any records of damage. It was also found in Cyprus in 1967 and nowadays is not considered a major pest. Its ability to cause an impact in the EU is uncertain considering the lack of evidence on impact in Cyprus and Greece. Phytosanitary measures are available to reduce the likelihood of entry. While the fulfilment of the criterion on having an economic or environmental impact in the EU is associated with a key uncertainty, all the other criteria assessed by EFSA for consideration as a potential quarantine pest are met.